A questão da ocupação urbana no Brasil nos anos 90: uma reflexão a partir dos dados da PNAD - Dedecca, Claudio Salvadori; Baltar, Paulo Eduardo de Andrade; Rosandiski, Eliane (Nova Economia, 2013)
A questão da ocupação urbana no Brasil nos anos 90: uma reflexão a partir dos dados da PNAD